A Fe5C2 nanocatalyst for the preferential synthesis of ethanol via dimethyl oxalate hydrogenation. Issue 39 (20th April 2017) - He, Jia; Zhao, Yujun; Wang, Yue; Wang, Junhu; Zheng, Jian; Zhang, Hanlei; Zhou, Guangwen; Wang, Chongmin; Wang, Shengping; Ma, Xinbin
Abstract : The Fe5 C2 nanocatalyst exhibits excellent catalytic activity with a significantly high selectivity of 89.6% to ethanol in gas-phase hydrogenation of dimethyl oxalate. Abstract : A Fe-based catalyst exhibits extremely high selectivity (89.6%) besides excellent catalytic activity in gas-phase dimethyl oxalate hydrogenation. The ethanol formation occurs via hydrogenation of methyl acetate instead of ethylene glycol over the active species Fe5 C2 .